MENGINVESTIGASI MODEL PEMBELAJARAN MUSLIM YANG EFEKTIF ANAK USIA DINI DIMASA PANDEMIC COVID-19 - Maryam Hasyim; Mirwan Surya Perdhana (Jurnal Ilmiah Ekonomi Islam, 2022)
The corona virus (Covid-19) that is hitting the world today is very influential on social and economic life, and even has an impact on the world of education. The Indonesian government has taken a policy which is stated in Government Regulation No. 21 of 2020. The article explains to limit school activities with BDR (Learning From Home) learning activities through the circular letter of the Minister of Education and Culture 36962/MPK.A/HK/2020 which stated that all learning must be done online to prevent the spread of the corona virus disease (Covid-19). The existence of government policies that enforce online learning ultimately requires parents to be able to guide their children to study at home and can replace teachers at school, so that parents play an important role in achieving online learning goals. This study specifically discusses the involvement of parent-teacher relationships in achieving effective learning models during the Covid-19 pandemic. This research is a qualitative research with a phenomenological method. The research population includes parents and teachers from kindergarten to elementary school grade 2 and the sample technique using Purposive Sampling includes 10 parents and 10 teachers. Qualitative data analysis consists of five stages including collecting data into a formal database (compile database), breaking down data in the database (disassemble database), reassembly (compiling), interpreting (interpreting data) and the last stage is providing conclusions (conclude). Research data processing consists of coding (coding), data classification (classify), followed by categorization or categorization, or also called in-vivo term or in-vivo coding. Government policies that enforce online learning in fact make children less able to understand the material so that learning becomes less effective. The results of the assessment found that the problem was that not all levels of education were able to support the implementation of education through the use of the internet. Some teachers in various regions also feel uneasy about the online learning model. This is inseparable from the importance of face-to-face learning which should be important for early childhood children. Learning that is applied during the pandemic shows a big change and tends to lead to a decline. This is because the educational model contradicts the educational goals that are applied and needed for early childhood who require a lot of interaction with other people. Keywords : Effectiveness of learning, online learning, phenomenology, basic education